Nurse-led digital health program for home blood pressure monitoring in stroke patients: protocol for a pooled analysis of randomized controlled trials - Zhang, Wei; Mei, Zubing; Feng, Zaibang; Li, Bin (Frontiers in Public Health, 2024)
Background: Hypertension is a major risk factor for stroke recurrence in stroke patients. Home blood pressure monitoring, facilitated by digital health technologies and led by nurses, may improve blood pressure control in this high-risk population. However, the evidence is not yet conclusive. This study protocol outlines a pooled analysis of the current literatures to evaluate the effectiveness of nurse-led digital health programs for home blood pressure monitoring in stroke patients. Methods and Analysis: We will conduct a comprehensive search of some major electronic databases (e.g., PubMed, EMBASE, Cochrane Library, and CINAHL) and trial registries for randomized controlled trials evaluating nurse-led digital health programs for home blood pressure monitoring in stroke patients. Two reviewers will independently screen titles and abstracts, review full-text articles, extract data, and assess risk of bias using the revised Cochrane risk-of-bias tool for randomized trials (RoB 2.0). The primary outcome measures will be changes in both systolic and diastolic blood pressure from baseline to the end of the intervention period. Secondary outcomes include adherence to the program, patient satisfaction, and stroke recurrence. Data will be pooled and analyzed using meta-analysis techniques, if appropriate. Discussion: This study will provide comprehensive evidence on the effectiveness of nurse-led digital health programs for home blood pressure monitoring in stroke patients. The findings could have substantial implications for clinical practice and health policy, potentially informing the development of guidelines and policies related to hypertension management and stroke prevention. Conclusions: By pooling the results of randomized controlled trials, this study will offer a robust evidence base to inform clinical practice and health policy in the context of stroke patients. Despite potential limitations such as heterogeneity among studies and risk of publication bias, the rigorous methodology and comprehensive approach to data synthesis will ensure the reliability and validity of the findings. The results will be disseminated through a peer-reviewed publication and potentially at relevant conferences.